2022
DOI: 10.1093/infdis/jiac246
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Reconstruction of Long-term Chikungunya Virus Circulation in Burkina Faso and Gabon

Abstract: Chikungunya virus (CHIKV) is a major public health concern worldwide. However, infection levels are rarely known, especially in Africa. We recruited individuals from Ouagadougou, Burkina Faso and Lambaréné, Gabon (age range: 1-55), tested their blood for CHIKV antibodies and used serocatalytic models to reconstruct epidemiological histories. In Ouagadougou, 291/999 (29.1%) individuals were seropositive, ranging from 2% among those <10y to 66% in those 40-55y. We estimated there were 7 outbreaks since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
(37 reference statements)
3
12
1
Order By: Relevance
“…A strong correlation of serostatus by household has also been observed with dengue virus [31]. Sex was another notable predictor, consistent with results from both Bangladesh and elsewhere that have consistently shown infection risk is higher among females [19,30,[32][33][34]. It has been suggested that 4 differences in mobility patterns may explain this increased risk, with women in Bangladesh spending more time in and around the home where mosquitoes reside [30].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A strong correlation of serostatus by household has also been observed with dengue virus [31]. Sex was another notable predictor, consistent with results from both Bangladesh and elsewhere that have consistently shown infection risk is higher among females [19,30,[32][33][34]. It has been suggested that 4 differences in mobility patterns may explain this increased risk, with women in Bangladesh spending more time in and around the home where mosquitoes reside [30].…”
Section: Discussionsupporting
confidence: 80%
“…To determine CHIKV seropositive we first calculated the ratio between the fluorescence intensity to CHIKV and the control MGMT protein, and used a cut point of 5.5 to identify those with a history of CHIKV exposure (Figure S1). It has previously been estimated that a ratio of 5.5 on a linear scale (~1.70 log scale) is the threshold for the MMIA to achieve 95% sensitivity and specificity (personal communication) [19].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Burkina Faso, DENV is the main endemic arbovirus included in the diagnostic and surveillance protocols, which explains the difficulty of obtaining CHIKV-positive samples. Only one seroprevalence study on CHIKV has been documented [ 16 ]. These multiplexed methods will help to improve early detection and effective surveillance of CHIKV in both humans and vectors.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, a prevalence of 28.54% of dengue fever was reported among pregnant women in Ouagadougou [ 15 ]. Another sero-epidemiological study of CHIKV was conducted in Ouagadougou, Burkina Faso, with blood samples collected in 2015, and a seroprevalence of 29.1% was reported [ 16 ]. These consecutive reports in different populations (general and pregnant populations) suggest a considerable dengue burden in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%